Evaluation of magnetic particle inspection for optimizing welding quality in back gouging boom structure preparation in heavy machinery - Aryswan, Adhe; Hasibuan, Apriansyah Sutan; Butar Butar, Hendra; Havwini, Tian; Gemala, Mega (Politeknik Negeri Lhokseumawe, 2025)
This study investigates the effectiveness of Magnetic Particle Inspection (MPI) in optimizing welding preparation for the back gouging of boom structures in hydraulic mining shovels. The primary objective is to evaluate MPI's efficiency in detecting surface and near-surface defects during the pre-welding stage, thereby improving the overall welding quality of boom structures, which play a critical role in supporting heavy loads. MPI is utilized as an initial inspection method prior to Ultrasonic Testing (UT), enabling early detection of potential defects and reducing the likelihood of failures during subsequent UT evaluations. The study reveals the presence of linear and rounded discontinuities that may compromise weld integrity. By applying MPI early in the process, the need for rework during UT is minimized, resulting in cost and time savings. Furthermore, the findings of this study contribute to supporting two key organizational initiatives—People, Quality, Velocity, Cost (PQVC) and Built-in Quality (BIQ)—which aim to enhance both the efficiency and reliability of the welding process.